Implementasi Pembelajaran Berdiferensiasi dalam Kurikulum Merdeka Pada Mata Pelajaran PAI dan Budi Pekerti - Helma, Helma; Satria, Rengga (Prodi Pendidikan Keagamaan Islam, 2025)
This research is motivated by the differences in students in various aspects which require teachers to carry out learning by paying attention to the differences that exist in students in a class or what is called differentiated learning. The aim of this research is to explain the extent to which teachers have implemented differentiated learning in Islamic Education and Character subjects in class X of SMK Negeri 4 Padang. This research uses a qualitative method with a case study approach. The research results show that the differentiated learning that has been implemented includes content, process, and product aspects that are in accordance with the differentiated learning indicators, although it is still not optimal and is hampered by several things. Differentiated learning is carried out as a form of appreciation for the diversity that exists in students